2011
DOI: 10.1111/j.1582-4934.2011.01330.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of telocytes in skeletal muscle interstitium: implication for muscle regeneration

Abstract: Skeletal muscle interstitium is crucial for regulation of blood flow, passage of substances from capillaries to myocytes and muscle regeneration. We show here, probably, for the first time, the presence of telocytes (TCs), a peculiar type of interstitial (stromal) cells, in rat, mouse and human skeletal muscle. TC features include (as already described in other tissues) a small cell body and very long and thin cell prolongations—telopodes (Tps) with moniliform appearance, dichotomous branching and 3D-network d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
201
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(223 citation statements)
references
References 73 publications
15
201
1
Order By: Relevance
“…The interalveolar region contained predominantly CD34‐positive cells on P30, with the formation of networks that separate the clusters of alveoli from each other and separate clusters of alveoli from the periurethral smooth muscle, thus attributing to the exclusively CD34‐positive interstitial cells uniquely a role of ICCs progenitor cells is a limited proposition, in view of the evidence that these cells possess many other functions in the tissue organisation and functionality in various organs 8, 10, 11, 12, 17, 18, 24, 25. CD34‐positive telocytes that do not express c‐Kit may also perform a pacemaker function 48, 49 via c‐Kit‐independent pathways, such as the SK3 pathway, by inhibiting electrical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interalveolar region contained predominantly CD34‐positive cells on P30, with the formation of networks that separate the clusters of alveoli from each other and separate clusters of alveoli from the periurethral smooth muscle, thus attributing to the exclusively CD34‐positive interstitial cells uniquely a role of ICCs progenitor cells is a limited proposition, in view of the evidence that these cells possess many other functions in the tissue organisation and functionality in various organs 8, 10, 11, 12, 17, 18, 24, 25. CD34‐positive telocytes that do not express c‐Kit may also perform a pacemaker function 48, 49 via c‐Kit‐independent pathways, such as the SK3 pathway, by inhibiting electrical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Telocytes may also exercise pacemaker function by means of the c‐Kit, but may also possess a supportive function for the contraction of periductal smooth muscle, possibly by means of c‐kit‐independent pathways, such as via the SK3 (small conductance calcium‐activated potassium Channel 3) pathway 20, 23. The function of telocytes varies between organs 8, 10, 11, 12, 17, 18, 24, 25, and their role in the prostate remains elusive, in addition to lack of information regarding the development of these cells in prostate tissue.…”
Section: Introductionmentioning
confidence: 99%
“…They secreted small signal molecules and shed microvesicles & exosomes that transfer macromolecules for repair of myocardial cells. So TCs might be key players in regeneration/repair of myocardium [46,48] .…”
Section: Discussionmentioning
confidence: 99%
“…The typical shape of telocytes with their prolongations ("telopodes") situated in the vicinity of nerves, vessels and cardiomyocyte progenitors suggests a role in intercellular signalling as regulators in myocardial regeneration and as "nursing cells" for cardiac progenitors (Gherghiceanu & Popescu). In a recent study, Popescu and his group have identified telocytes also in skeletal muscle tissue (Popescu 2011). Beside their typical prolongations, telocytes are known to express c-kit and caveolin-1, but are Pax7 negative and thus differ from the satellite cell population.…”
Section: Cell Source 31 the Satellite Cellmentioning
confidence: 99%